Faktor-faktor Internal yang Memengaruhi Financial Distress pada Perusahaan Sektor Industri Barang Konsumsi yang Terdaftar di BEI Tahun 2015-2019 - Sari, Andini; Hartono, Ulil (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2020)
Financial distress that occurs on an ongoing basis will have a bankruptcy impact on the company, for that we need an analysis related to the factors that influence it. This study aims to determine the factors that influence financial distress in the consumer goods industry sector. Predictors used as independent variables are financial ratios which include liquidity, leverage, and profitability as well as ownership structures which include managerial ownership, institutional ownership, and foreign ownership to predict the possibility of a company experiencing financial distress. The Kind of research used is causal associative. The sample retrieval technique used is purposive sampling, samples in the study were obtained as many as 10 companies in the consumer goods industry sector which were listed on the Indonesia Stock Exchange in the period 2015-2019. The data analysis technique used is logistic regression. The result showed that leverage and profitability had a negative effect on financial distress, while other variables namely liquidity, managerial ownership, institutional ownership, and foreign ownership did not have an influence on the probability of financial distress. Therefore, companies in the consumer goods industry sector are expected to pay more attention to the value of leverage and profitability to prevent the company from financial distress.